Inactivation of PI3K-C2α deregulates cell death pathways and sensitizes to endotoxic shock - York Posor; Sarah E. Conduit; Wayne Pearce; Daniele Morelli; Georgia Constantinou; Maria Whitehead; Neil J. Sebire; Cheryl L. Scudamore; Nieves Peltzer; Henning Walczak; Bart Vanhaesebroeck (Proceedings of the National Academy of Sciences, 2025)
The organismal roles of the class II PI3K isoform PI3K-C2α remain poorly understood. Recent studies have found PI3K-C2α to promote arterial thrombosis and breast cancer metastasis, generating interest in this kinase as a drug target, with small molecule PI3K-C2α inhibitors now available. However, the consequences of systemic PI3K-C2α inactivation in the nondiseased, postnatal state are largely unknown. Here, we show that induction of genetic PI3K-C2α inactivation in adult mice is well tolerated, without adverse effects on normal physiology. Surprisingly, however, mice with inactive PI3K-C2α display strong sensitization to challenge with bacterial lipopolysaccharide (LPS), a model of endotoxic shock. This sensitization is recapitulated by vascular endothelial-specific deletion of PI3K-C2α. Furthermore, sensitization to LPS can be fully rescued by disabling extrinsic induction of cell death by combined caspase-8- and RIPK3 deficiency. These observations validate the tolerability of systemic PI3K-C2α inhibition in principle but reveal an unexpected role for PI3K-C2α in the regulation of extrinsic cell death pathways.